2019
DOI: 10.1016/j.jpsychores.2019.109761
|View full text |Cite
|
Sign up to set email alerts
|

Emotional outcomes in clinically isolated syndrome and early phase multiple sclerosis: a systematic review and meta-analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Patients with CIS are already afflicted by fatigue and depression, typically of milder severity than in relapsing–remitting MS (RR-MS) patients [ 20 , 21 ]. Although several studies demonstrated a relationship between fatigue and depression symptomatology and brain function alterations in RR-MS patients [ 15 , 18 , 19 , 22 ], there is no direct evidence for such a relation in CIS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CIS are already afflicted by fatigue and depression, typically of milder severity than in relapsing–remitting MS (RR-MS) patients [ 20 , 21 ]. Although several studies demonstrated a relationship between fatigue and depression symptomatology and brain function alterations in RR-MS patients [ 15 , 18 , 19 , 22 ], there is no direct evidence for such a relation in CIS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the risk to develop depression is two or five-times higher for MS patients than general population, with a lifetime prevalence of 50%, a rate of 44,5% during relapses but with no differences in terms of gender (Feinstein, 2011). In a recent meta-analysis, depressive symptoms have been reported in 35% of CIS and in the early phase of MS (Rintala et al, 2019). They may occur even in the absence of physical disability, sometimes anticipating the onset of clinical deficits (Haussleiter et al, 2009;Lo Fermo et al, 2010), suggesting that mood disturbances are not a reactive phenomenon to the pathology, but a considerable part of it (Feinstein et al, 2014).…”
Section: Depressive Symptoms In Msmentioning
confidence: 99%
“…We found elevated scores of depression and anxiety in MS patients consistent with the previous research 4,7 also in line with a study in early phase MS. Symptoms of anxiety are comparable or even marginally higher in early stages relative to later stages of MS 37 . Our findings suggest that, in the early phase of cognitively preserved MS patients, higher anxiety and lower purposefulness (SD2) significantly impacted depression symptoms.…”
Section: Discussionmentioning
confidence: 90%